Pollution-Reducing and Resource-Saving Technological Progress - Dagmar Nelissen; Till Requate (Kiel University, Department of Economics, 2004)
In this paper we survey the theoretical literature on both pollution-reducing and resource-saving technological progress. The literature can be divided into two strands. One strand deals with microeconomic models which investigate incentives to adopt and to develop environmentally more friendly technologies for different policy tools and in different economic environments, such as market structure or timing and commitment structures. It turns out that, firstly, price based instruments such as emission taxes and tradable permits perform better than command and control policies, and secondly, that under competitive conditions ex ante end ex post optimal policies are equivalent. Under imperfect market conditions the policy conclusions are more subtile. The second strand of literature deals with both pollution-reducing and resource-saving technological progress within endogenous growth models. Most of these models are characterized by three market imperfections : market power for new (intermediate) products, positive R&D spillovers, and pollution. These imperfections can be mitigated by subsidies on intermediate products, subsidies on R&D effort, and a tax on emissions. Moreover, in most models there occurs a trade-off between the speed of growth and environmental quality.
Keywords: 330; pollution-reducing technological progress; resource-saving technological progress; environmental innovation; endogenous growth models; Technischer Fortschritt; Umwelttechnik; Innovation; Energiesparen; Neue Wachstumstheorie; Ökosteuer; Umweltabgabe; Emissionsrechte; Theorie